DEVELOPMENT OF PRICES AND MARKET INTEGRATION OF RED CHILLIES (Capsicum annuum L.) IN MALANG REGENCY, MALANG CITY, AND SURABAYA CITY - Ridayati Ridayati; Sujarwo Sujarwo; Fahriyah Fahriyah (Agricultural Socio-Economics Journal, 2022)
Red chilli (Capsicum annumm L.) is a commodity with high price fluctuations. Market participants use red chilli price fluctuations to manipulate price information and cause information asymmetry. So that, the price information is not transmitted properly and indicates the market is not integrated. This study aims to describe price developments and analyze the integration of the red chilli market in Malang Regency, Malang City, and Surabaya City. The analytical method used is descriptive statistics, Johansen cointegration, and Vector Error Correction Model (VECM). The results showed that the price of red chilli fluctuated. Red chilli price fluctuations occur because production is seasonal, causing the distribution of chillies to be uneven every month. Therefore, efforts are needed to regulate cropping patterns so that the supply of chilli is always available. The results of market integration show that all variables are cointegrated in the long run and not integrated into the short run. This indicates that price information is transmitted imperfectly. Therefore, it is necessary to improve the information system so that all market participants can access market information.